Mechanical power, thrust power and propelling efficiency: relationships with elite sprint swimming performance - Gatta, G.; Cortesi, M.; Swaine, I.; Zamparo, P. (Journal of Sports Sciences, 2018)
The purpose of this study was to explore the relationships between mechanical power, thrust power, propelling efficiency and sprint performance in elite swimmers. Mechanical power was measured in 12 elite sprint male swimmers: (1) in the laboratory, by using a whole-body swimming ergometer (W'TOT) and (2) in the pool, by measuring full tethered swimming force (FT) and maximal swimming velocity (Vmax): W'T = FT · Vmax. Propelling efficiency (etaP) was estimated based on the "paddle wheel model" at Vmax. Vmax was 2.17 ± 0.06 m/s, etaP was 0.39 ± 0.02, W'T was 374 ± 62 W and W'TOT was 941 ± 92 W. Vmax was better related to W'T (useful power output: R = 0.943, P < 0.001) than to W'TOT (total power output: R = 0.744, P < 0.01) and this confirms the use of the full tethered test as a valid test to assess power propulsion in sprinters and to estimate swimming performance. The ratio W'T/W'TOT (0.40 ± 0.04) represents the fraction of total mechanical power that can be utilised in water (e.g., etaP) and was indeed the same as that estimated based on the "paddle wheel model"; this supports the use of this model to estimate etaP in swimming.